PERATURAN BERSAMA MENTERI AGAMA DAN MENTERI DALAM NEGERI NOMOR 08 DAN 09 TAHUN 2006 TENTANG PENDIRIAN RUMAH IBADAT (KAJIAN DALAM PERSPEKTIF HAK ASASI MANUSIA ) - Benny Asrianto (Lembaga penelitian dan pengabdian kepada masyrakat, 2010)
Pundamental 1945 Constitution as the rule has been set explicitly for religious freedom in the run by followers, who belong to one human rights has, but in reality the persecution of religious life and often inevitable. Between religious persecution can come from various directions such as harassing each other, mutual intimidate(violence) and that most often occurs between religious persecution that is prihal establishment synagogue. Therefore, in terms of the establishment of the synagogue there must be government intervention to regulate it, if in this case given the freedom and without any clear rules, the sectarian conflict will not be able to avoid. One step from the government to avoid conflict in the establishment of the synagogue is to be issued the Joint Decree of the Minister of Religious Affairs and the Minister of Home Affairs Number 08 and Number 09 Year 2006 About the Construction of Houses of Worship that aims to create harmony and peace between religious and have certainty Strong law.